Ecdysteroids regulate the levels of Molt-Inhibiting Hormone (MIH) expression in the blue crab, Callinectes sapidus. - Sirinart Techa (PLoS ONE, 2015)
Arthropod molt is coordinated through the interplay between ecdysteroids and neuropeptide hormones. In crustaceans, changes in the activity of Y-organs during the molt cycle have been regulated by molt-inhibiting hormone (MIH) and crustacean hyperglycemic hormone (CHH). Little has been known of the mode of direct effects of ecdysteroids on the levels of MIH and CHH in the eyestalk ganglia during the molt cycle. This study focused on a putative feedback of ecdysteroids on the expression levels of MIH transcripts using in vitro incubation study with ecdysteroids and in vivo RNAi in the blue crab, Callinectes sapidus. Our results show a specific expression of ecdysone receptor (EcR) in which EcR1 is the major isoform in eyestalk ganglia. The initial elevation of MIH expression at the early premolt stages is replicated by in vitro incubations of eyestalk ganglia with ecdysteroids that mimic the intrinsic conditions of D0 stage: the concentration (75 ng/ml) and composition (ponasterone A and 20-hydroxyecdysone at a 3:1 (w:w) ratio). Additionally, multiple injections of EcR1-dsRNA reduce MIH expression by 67%, compared to the controls. Our data provide evidence on a putative feedback mechanism of hormonal regulation during molting cycle, specifically how the molt cycle is repeated during the life cycle of crustaceans. The elevated concentrations of ecdysteroids at early premolt stage may act positively on the levels of MIH expression in the eyestalk ganglia. Subsequently, the increased MIH titers in the hemolymph at postmolt would inhibit the synthesis and release of ecdysteroids by Y-organs, resulting in re-setting the subsequent molt cycle.